2022
DOI: 10.15264/cpho.2022.29.2.92
|View full text |Cite
|
Sign up to set email alerts
|

Anakinra to Mitigate Hemophagocytic Lymphohistiocytosis-Like Toxicity Following Chimeric Antigen Receptor T-cell Therapy in Pediatric B-cell ALL

Abstract: Hemophagocytic lymphohistiocytosis-like toxicity following chimeric antigen receptor (CAR)-T cell therapy (carHLH) is a rare and fulminant complication. Currently, there are neither well-established diagnostic criteria nor optimal treatment option for carHLH. Given the similarities of hyperinflammatory process and cytokine profiles between cytokine release syndrome (CRS) and carHLH, tocilizumab and corticosteroids are the suggested front-line treatment options for both conditions. However, when carHLH is refra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Secondary HLH can occur in patients with severe infection, malignancy, or autoimmune disease, and is rarely associated with allogeneic hematopoietic stem cell transplantation and CAR T-cell therapy. Reports on HLH-like toxicity following CAR T-cell therapy (carHLH) are increasing, with fever, organomegaly, jaundice, gastrointestinal problems, and pulmonary complications being the major clinical features [ 18 , 41 - 43 ]. Although the incidence of carHLH is relatively rare (3–4%) [ 44 ], it has a high mortality rate.…”
Section: Hemophagocytic Lymphohistiocytosis-like Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary HLH can occur in patients with severe infection, malignancy, or autoimmune disease, and is rarely associated with allogeneic hematopoietic stem cell transplantation and CAR T-cell therapy. Reports on HLH-like toxicity following CAR T-cell therapy (carHLH) are increasing, with fever, organomegaly, jaundice, gastrointestinal problems, and pulmonary complications being the major clinical features [ 18 , 41 - 43 ]. Although the incidence of carHLH is relatively rare (3–4%) [ 44 ], it has a high mortality rate.…”
Section: Hemophagocytic Lymphohistiocytosis-like Toxicitymentioning
confidence: 99%
“…Data regarding the clinical use of anakinra in children with carHLH are limited, and treatment guidelines for it have not yet been established. Anakinra is typically added to advanced CRS as a second-line treatment, and studies have shown that it may be effective in controlling CAR T-cell therapy-associated toxicities by suppressing inflammatory pathways [ 17 , 41 , 43 , 46 ]. Although the optimal dose and treatment duration has not been determined, a starting dose of 2 mg/kg subcutaneously or intravenously every 6 h (8 mg/kg/day, maximum daily dose of 400 mg) is administered from days to weeks, based on protocols used in autoimmune or rheumatic diseases [ 47 , 48 ].…”
Section: Hemophagocytic Lymphohistiocytosis-like Toxicitymentioning
confidence: 99%
“…CRS tendency to progress into or overlap with HLH makes lymphohistiocytosis more challenging in its management. HLH manifests itself mainly with fever, jaundice, organomegaly, as well as gastrointestinal and pulmonary problems [140,141]. Although diagnostic criteria for carHLH were suggested, such as peak serum ferritin level and development of organ failure (hepatic, renal, pulmonary), the scale is for now recommended for adults only and needs adjustment for pediatric patients [142].…”
Section: Hemophagocytic Lymphohistiocytosismentioning
confidence: 99%